DETERMINATION OF THE INFECTIVE STRAIN OF HYDATID CYST IN IRAQI CATTLE BY USING CO1 GENE - Muhaidi, M. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Hydatid Cysts were obtained from liver, lungs, spleen, heart, and peritoneal cavity of 15 cows, from different Iraqi regions between December 2014 and October 2015. Hydatid cysts (protoscoleces) were used for mitochondrial DNA extraction by using mechanical grinder, and the purification of mtDNA was done by (promega kit, USA). "The mitochondrial cytochrome c oxidase subunit 1 (CO1) gene" was used as target for "polymerase chain reaction (PCR)" which successfully amplified the targeted this gene with 450 bp. The PCR products were purified and partial sequences were determine. The obtained sequences were aligned with the corresponding region of co1 gene in the Gene Bank nucleotide database to confirm the infection with hydatid cyst sheep strain (G1) in Iraq. The amplified CO1 targeted region was analyzed to obtain the phylogenetic tree. G1 genotype was the most common strain and the actual source of infection of Iraqi’s cattle. All of 15 samples were G1 strain (sheep strain) according to the partial sequences of (CO1) genes.